Determining the Efficacy and Safety of Teneligliptin and Metformin Versus Glimepiride and Metformin in Patients of Type-2 Diabetes Mellitus Uncontrolled with Monotherapy - Nitika Hans (Technological Innovation in Pharmaceutical Research Vol. 10, 2021)
Introduction: Type 2 diabetes mellitus is one of the most common non- communicable diseases associated with short term and long term complications. Material and Methods: A total of 60 patients were included in the study divided into 2 groups of 30 patients each. Group 1 patients were given Teneligliptin 10 mg once a day and metformin 500 mg twice a day after meals for 12 weeks. Group 2 patients were given Glimepiride 1 mg once a day and metformin 500 mg twice a day after meals for 12 weeks. After the written consent, history, clinical examination, biochemical investigations including FBG, PPBG, HbA1c and lipid profile were done. Repeat FBG and PPBG were done every week upto 12 weeks. HbA1c and lipid profile were done at the beginning and at the end of study. Results: Change in FBG was more in group 1 as compared to group 2. On comparison of reduction in change in PPBG in patients of group 1 versus group 2, there was a highly significant reduction in group 1. Change in HbA1c, total cholesterol levels, triglyceride levels, HDL and LDL was more in group 1 than in group 2. Conclusion: Teneligliptin and metformin caused a greater improvement in glycaemic and lipid profile as compared to Glimepiride and metformin. Thus teneligliptin is more efficacious than glimepiride.